2011
DOI: 10.4040/jkan.2011.41.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Web-based Education Program to Prevent Secondary Stroke

Abstract: Purpose: This study was conducted to develop and evaluate a web-based education program for secondary stroke prevention. Methods: A web-based secondary stroke prevention education program was developed using the system's life cycle methods and evaluated by comparing the effects of education among three groups, a web group, a booklet group and a control group. Results: Knowledge level of both patients and family, as well as some health behavior compliance in the web-bas ed and booklet education groups were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 13 publications
1
28
1
2
Order By: Relevance
“…The program contents were based on previously conducted domestic studies [ 6 ] and consisted of stroke and nutrition education as well as exercise guidance. The 12-week program included a stroke education class once a week, a nutrition management class once a week, and exercise guidance 3 times a week.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The program contents were based on previously conducted domestic studies [ 6 ] and consisted of stroke and nutrition education as well as exercise guidance. The 12-week program included a stroke education class once a week, a nutrition management class once a week, and exercise guidance 3 times a week.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, one of the most important goals of nursing is to prevent stroke occurrence [ 5 ]. To prevent stroke from occurring, stroke risk factors in at-risk subjects should be controlled and the diseases causing stroke should be managed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Kim ). Studies on web‐based education and nursing interventions in Korea have shown that the programmes improve patient knowledge, self‐care proficiency and health (Jung , Kim , Kim & Park ).…”
Section: Introductionmentioning
confidence: 99%
“…최근 인구의 고령화와 더불어 뇌졸중 환자의 생존율은 증가하였으나, 재발률이 약 20%로 재발할 경우 치명적인 결과를 초래할 수 있다 [2]. 이러한 측면에서 2010년 이후에는 뇌졸중의 재발예방 [7], 건강행위 [8], 자기 관리 [9,10] …”
unclassified